Literatur und Diskurs-Kreativität. Zur Deutscholympiade in Polen - ORŁOWSKI, Hubert (Wydawcnictwo Naukowe UAM, 1994)
The author begins his article by presenting the German Language Olympic in Poland and refers very detailed the process and the results of it. This describing is however only a starting point for his considerations about the didactic of literature in Polish schools. Further the author gives a significant analysis of different trends in the history of literature and in the interpretation of literary texts and demands the change of present situation in the subject: Polish and general literature, because a lot of Polish learners choose German as first or second foreign language but their interests are conditioned not by German literature or culture but by German economy.